Empirical methods in the economics of international immigration - Fernando A. Lozano; Michael D. Steinberger (Institute for the Study of Labor (IZA), 2010)
In this chapter we provide a brief overview of the main empirical tools used by economists to study international migration. We begin by exploring the three broad research areas that economists examine when researching immigration. We then explore the strengths and shortcomings of the standard methods, and highlight new methods that will likely become more common in future work in the field. We divide the most common tools used in the empirical literature into four broad categories: (1) Ordinary Least Squares and Inference, (2) Difference-in-Difference Estimation, (3) Instrumental Variables Techniques, and (4) Recent Developments and Distributional Estimators. We use recent empirical work to highlight and explain each method, and provide sources for researchers interested in further information on each topic.
Keywords: F22; 330; immigration; empirical methods